Climate-Smart Agriculture in Kyrgyzstan - World Bank; International Center for Tropical Agriculture (2018)
The CSA profile for the Kyrgyz Republic was developed with funding from the Global Facility for Disaster Reduction and Recovery (GFDRR) (see https://www.gfdrr.org/en/who-we-are).